Covalently immobilized triphenylphosphine rhodium complex: synthesis, characterization, and application in catalytic olefin hydrogenation - Wang, Lei; Jia, Mingjun; Shylesh, Sankaranarayanapillai; Philippi, Thomas; Seifert, Andreas; Ernst, Stefan; Singh, Anand Pal; Thiel, Werner R. (Chemcatchem, 2010)
A trimethoxysilane functionalized triphenylphosphine was coordinated to rhodium(I) and the resulting rhodium complex was covalently bound to a mesoporous SBA-15 support. The catalytic activity of this hybrid material was studied for the hydrogenation of 2-cyclohexen-1-one and compared with the corresponding homogeneous catalyst. According to the (31)P-MAS NMR data, the catalytically active species was stable against oxidation; no structural change could be detected after exposing it to air for more than two months. Transmission electron microscopy (TEM) measurements on the used catalyst confirmed that the rhodium species was also stable against reduction to the metal because the formation of rhodium nanoparticles during the catalysis could be excluded. The kinetic curves of the recycled system confirmed that this hybrid catalyst shows excellent activity, selectivity, stability, and reusability, and is truly heterogeneous in the hydrogenation reaction.
Keywords: alkenes; heterogeneous catalysis; Hydrogenation; mesoporous materials; Rhodium